Analisis Persebaran Kasus Diare dan Tuberkulosis di Kabupaten Rembang Berbasis Sistem Informasi Geografis (SIG) Tahun 2023-2024 - Naila Amelia Shahada; Bambang Agus Herlambang; Ahmad Khoirul Anam (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2026)
Diarrhea and Tuberculosis (TB) remain significant public health problems in Indonesia, including Rembang Regency. This study aims to analyze the spatial distribution and temporal changes of Diarrhea and TB cases in Rembang Regency during 2023–2024 using a Geographic Information Sistem (GIS) approach. A descriptive-analytic method was applied using secondary data, including administrative boundary shapefiles, disease case data, and health facility data at the sub-district level. Spatial processing and analysis were conducted using QGIS to produce thematic maps and compare disease distribution patterns between years. The results indicate that Diarrhea and TB cases were unevenly distributed across sub-districts and formed distinct spatial patterns. Case changes between 2023 and 2024 varied spatially, reflecting dynamic disease trends. The integration of disease maps with health facility distribution shows that areas with high case numbers were not always supported by adequate health facilities. The implementation of GIS-based maps into a web platform enhances accessibility and supports spatial-based public health decision-making.